Chatbots in Malaysia –A Balanced Scorecard Approach - Wen Jyng, Lai; A Rubasundram, Geetha (International Journal of Psychosocial Rehabilitation, 2020)
This research provides an insight of the adoption of chatbots among businesses in Malaysia. With technological advancements, there has been a growth in the adoption of chatbots by firms. Businesses and individuals are more receptive towards the idea of using chatbots as their communication and service tool for basic or repetitive information. However, since it is still at an initial stage, assessing the impact of the chatbot adoption may not be prevalent in terms of financial performance only. Hence, this research uses the Balanced Scorecard angle of assessing the non-financial angles (Stakeholders, Internal Process and Learning & Growth) against the Financial Performance of a firm. Questionnaires were sent out to Malaysian firms to assess their experience with the chatbot adoption. The results reflected a positive attitude from stakeholders towards the firms adoption of chatbots. It also highlighted that key decisions and information pertaining towards the decision to adopt chatbots may not have been strongly discussed with shareholders or with the support of directors. It also revealed that due to the chatbot implementation still being at an infancy stage, key impacts towards employees such as unemployment or retraining was not yet worrying. Overall, the performance was perceived to have improved after the implementation of chatbots in the firm, though certain areas of improvements were also highlighted